2021
DOI: 10.1002/eji.202149290
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2‐reactive T‐cell receptors isolated from convalescent COVID‐19 patients confer potent T‐cell effector function

Abstract: Both B cells and T cells are involved in an effective immune response to SARS-CoV-2, the disease-causing virus of COVID-19. While B cells-with the indispensable help of CD4 + T cells-are essential to generate neutralizing antibodies, T cells on their own have been recognized as another major player in effective anti-SARS-CoV-2 immunity. In this report, we provide insights into the characteristics of individual HLA-A*02:01-and HLA-A*24:02restricted SARS-CoV-2-reactive TCRs, isolated from convalescent COVID-19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Although there are many studies using infected animals for COVID-19 research, 87,88 only a few studies performed scRNA-seq on COVID-19-infected animals like monkeys, 89 hamsters, 90 macaques, 91 ferrets, 92 and K18-hACE2 transgenic mice. 93 Several studies demonstrated the antiviral immune responses of animal models after receiving newly developed vaccines with scRNA-seq, [94][95][96][97] revealing induced gene modules of different immune cell populations. As it is much easier to obtain samples from various organs in animal models than in human patients and at consecutive time points after COVID-19 infection, vaccination, or therapy, performing temporalspatial analysis at the single-cell resolution in animal models for COVID-19 could be a promising future direction.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Although there are many studies using infected animals for COVID-19 research, 87,88 only a few studies performed scRNA-seq on COVID-19-infected animals like monkeys, 89 hamsters, 90 macaques, 91 ferrets, 92 and K18-hACE2 transgenic mice. 93 Several studies demonstrated the antiviral immune responses of animal models after receiving newly developed vaccines with scRNA-seq, [94][95][96][97] revealing induced gene modules of different immune cell populations. As it is much easier to obtain samples from various organs in animal models than in human patients and at consecutive time points after COVID-19 infection, vaccination, or therapy, performing temporalspatial analysis at the single-cell resolution in animal models for COVID-19 could be a promising future direction.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Antigen-primed T cells are crucial to effectively countering the SARS-CoV-2 infection mediated by both CD4 + and CD8 + Teff cells ( 66 ). T cell response investigated against nucleocapsid (N) protein has been shown to exhibit robust IFN-γ response after 17 years of SARS-CoV infection against N peptides.…”
Section: Generation Of Antigen-primed T Cells During Natural Covid-19...mentioning
confidence: 99%
“…So far, T cells are considered to have a dominant role in the control and clearance of SARS‐CoV‐2 infection [ 14 , 15 ]. Several cases of fully recovered SARS‐CoV‐2 infection in patients with genetic or pharmacological B cell depletion for the unrelated condition have been reported, suggesting that a protective immune response against SARS‐CoV‐2 can be produced even without humoral immunity [ 16 , 17 ].…”
mentioning
confidence: 99%